Groundwater quality concern for wider adaptability of novel modes of Managed Aquifer Recharge (MAR) in the Ganges Basin, India - Jha, S. K.; Mishra, V. K.; Verma, C.L.; Sharma, Navneet; Sikka, Alok; Pavelic, Paul; Sharma, Parbodh Chander; Kant, L.; Sharma, Bharat R. (Elsevier, 2021)
Groundwater (GW) depletion and recurring floods have become a major concern among researchers and planners across the world. To rejuvenate stressed aquifer and moderate flood impacts, a modified version of managed aquifer recharge (MAR) consisting of a cluster of ten recharge wells (RWs) embedded in a community pond with an area of 2625 m2 and utilizing diverted floodwater was tested on a pilot scale in Ramganga sub basin, India. The approach could recharge a maximum of 72426 m3 of floodwater in 78 days during the wet season. The pond intervention minimized clogging of RWs by retaining maximum silt load of 68.01%. Hydro-geochemically, majority of water samples were of Mg-HCO3 and Ca-HCO3type. Ion exchange processes and weathering of carbonate and silicates were the controlling factors, determining water quality of the area. Total dissolved solids, fluoride, iron, zinc, manganese, chromium, cobalt, nickel, mercury, phosphate, nitrate, and ammonical nitrogen were found within the permissible limits as laid down by World Health Organization except arsenic and lead, which seems to be the inherent problem in the area, as evidenced by water quality analysis of farmers tube wells located upstream and down streams of the recharge site. The coliform presence in the 88.23% of sampled GW may thwart from direct use for drinking whereas it was fit for irrigation. Looking the benefits of modified MAR as a proactive GW quality improvement with good aquifer recharge, it is recommended for scaling up of the intervention across the GW stressed parts of the whole Ram Ganga basin and similar hydro-geological regions elsewhere.